The Brutality Of Krueger In Samuel Bayer's A Nightmare On Elm Street Movie (2010): A Psychoanalytic Perspective - ASANI, IPUNG (2012)
ABSTRACT IPUNG ASANI. A320080004. THE BRUTALITY OF KRUEGER IN SAMUEL BAYER'S A NIGHTMARE ON ELM STREET MOVIE (2010): A PSYCHOANALYTIC PERSPECTIVE. RESEARCH PAPER. MUHAMMADIYAH UNIVERSITY OF SURAKARTA. 2012. This study is aimed to explore the brutality of the major character on his life. The objective of the research is to analyze the major character based on its structural elements and psychoanalytic perspective. In analyzing the psychoanalytic aspects, the researcher applies the theory of psychoanalysis proposed by Sigmund Freud. The researcher employs the qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is A Nightmare on Elm Street movie directed by Samuel Bayer released in 2010. While the secondary data sources are other materials taken from books, journal, essay, and internet related to the study. The results of this study are as follows. Firstly, the structural elements of the movie present a unity. It appears in the beginning, middle, and end of the story. Secondly, the psychoanalytic analysis shows the phenomenon of brutality which is done by the major character. He always comes and kills the children from Preschool through their dream. Finally, the psychoanalytic analysis shows that brutality which is done by him happened because of his revenge. The revenge of him as a victim of being burnt alive by the parents of the children in Badham Preschool.